Implementing the Realistic Mathematics Education (RME) Approach to Three-Dimensional Shapes Characteristics using Traditional Blitar Souvenirs in Elementary Schools - Rahmawati, Ika; Kinarsih, Tri; Wiryanto, Wiryanto (research, training and philanthropy institution Natural Aceh, 2025)
The importance of the right approach to mathematics learning. Many students believe that mathematics is complicated to learn because many mathematics teachers teach abstractly. This research is qualitative descriptive research that uses Graveimeiijeir's design research method. This research aims to prove that the hypothesis that has been written in the hypothetical learning trajectory or HLT (Hypothetical Learning Trajectory) is correct and how it impacts students' understanding of the material on the characteristics of three-dimensional shapes using traditional Blitar souvenir media and LKPD, which function as a guide to student activities. This research was conducted at SDN Lidah Kulon IV in class 5B. The research subjects were five students, three men and two women. The research stages carried out were planning, implementation in the classroom, and data analysis. This research shows that learning activities using the RME approach are based on the stages of the iceberg theory. This stage consists of real-world situations, models that describe problem situations (models of), models for solving problems (models for), and formal mathematical stages. Using traditional Blitar souvenir media, this stage can help students understand material about the characteristics of three-dimensional shapes.